Method for deep purification of titanium sulfate solution of titanium dioxide by sulfuric acid method and bifunctional mesoporous silica adsorbent

CN122582637APending Publication Date: 2026-08-18PANZHIHUA XINGZHONG TITANIUM IND CO LTD +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202610987709.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-03
Publication Date
2026-08-18

AI Technical Summary

Technical Problem

[0007]本发明要解决的技术问题包括:(1)现有硫酸法钛液净化工艺对V、Cr、Mn的选择性较差,致使最终产品白度、消色力及色稳定性不足;(2)现有包膜路线易引入新杂质组分;(3)胺类萃取剂体系溶剂损失大、第三相严重,工业化适应性不足;(4)单一螯合基团修饰的介孔吸附材料在含高浓度Fe2+的强酸钛液体系下,难以实现V/Cr/Mn多杂质同时高效深度去除

Benefits of technology

[0054] (1) The present invention significantly improves the selectivity of impurity removal without affecting Ti 3+ Under the given concentration and F value conditions, deep synergistic removal of V, Cr, and Mn is achieved, with removal rates of over 80% for all three impurities (in the preferred embodiment, V/Cr/Mn removal rates are approximately 90%/85%/83%, respectively). This is significantly higher than conventional crystallization-reduction processes and single-group modified adsorbent schemes, and also achieves the removal of Fe. 2+ Highly selective rejection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122582637A_ABST
    Figure CN122582637A_ABST
Patent Text Reader

Abstract

The application discloses a kind of sulphuric acid method titanium dioxide titanium liquid vanadium chromium manganese depth purification method and bifunctional mesoporous silica adsorbent, belong to titanium dioxide technical field.The application is with amino methylene phosphonic acid / 8-hydroxyquinoline bifunctional mesoporous silica adsorbent as adsorption material, under ORP-150 to-80mV, temperature 45~55 ℃, to sulphuric acid method titanium liquid is carried out multistage series connection adsorption purification, realizes the selective adsorption of V, Cr, Mn, V≤5mg / L in titanium liquid after purification, Cr≤8mg / L, Mn≤15mg / L, removal rate all reach 80% or more, the rutile type titanium dioxide prepared in whiteness, colour strength and color stability under ultraviolet irradiation condition etc.All have obvious promotion, adsorbent can be recycled, it is suitable for clean production of high-quality rutile type titanium dioxide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of titanium dioxide technology, specifically relating to a method for deep purification of vanadium, chromium and manganese in titanium liquid from sulfuric acid process titanium dioxide and a bifunctional mesoporous silica adsorbent, so as to achieve deep removal of vanadium, chromium and manganese colorimetric heavy metal impurities in titanium liquid through chelation adsorption. Background Technology

[0002] Titanium dioxide is the inorganic white pigment with the best comprehensive performance and the largest usage. The sulfuric acid process is one of the main production processes at home and abroad. The raw materials are mainly ilmenite or acid-soluble titanium slag. The final product is obtained by successively going through the following processes: grinding, acid hydrolysis, leaching, iron filings reduction, sedimentation and filtration, vacuum crystallization to separate ferrous sulfate, hydrolysis, bleaching, salt treatment, calcination, wet grinding, coating, organic surface treatment, and air jet pulverization.

[0003] In addition to TiO2 and Fe2O3, titanium concentrate and acid-soluble titanium slag also contain colorimetric heavy metal impurities such as vanadium, chromium, and manganese. Their valence state and chemical form in the raw ore vary depending on the ore source (vanadium is mainly composed of vanadium). 3+ / V 4+ / V 5+ Chromium exists in a mixture of various oxidation states, and is usually in the form of Cr. 3+ Mainly Cr, with a small amount of Cr 6+ Coexistence, manganese mainly exists as Mn 2+ / Mn 3+ (Existing in form). After the raw ore is acidified with concentrated sulfuric acid, the above-mentioned impurities enter the acidification solution; after further reduction with iron filings, the titanium solution system is in a strongly reducing environment (Ti coexists). 3+ 1.5~3.0g / L and Fe 2+ 28~35 g / L), Cr 6+ With V 5+ All were rapidly reduced, and ultimately, vanadium in the reduced titanium solution was mainly in the form of VO. 2+ (V) 4+ It exists in the form of (accompanied by a small amount of V) 3+ ), all chromium is Cr 3+ Manganese exists in the form of Mn 3+ The aforementioned reduced impurities partially migrate with Fe in subsequent processes. 2+ The ferrous sulfate was removed by vacuum crystallization, but a considerable proportion still followed the Ti. 4+ Upon entering the hydrolysis stage, the titanium dioxide is ultimately captured by the metatitanic acid lattice or adsorbed by the grain boundaries, resulting in the following technical problems in the final rutile titanium dioxide product: (1) low whiteness and bleaching power; (2) significant photochromism: during the calcination process of the finished titanium dioxide, some residual transition metal impurities (especially V / Cr) can be oxidized by air to regenerate V. 5+ / Cr 6+These high-valence ions interact with the TiO2 lattice, and the color of titanium dioxide changes from white to light yellow / gray under ultraviolet light irradiation. After leaving the light source, it partially recovers, affecting the appearance stability of the product; (3) Insufficient weather resistance: Vanadium, chromium and manganese transition metal ions can act as photogenerated carrier traps, which intensifies the photocatalytic activity of titanium dioxide and causes its light retention rate to decrease under accelerated aging conditions.

[0004] For iron removal, existing processes are relatively mature, such as the leaching-reduction-temperature control process disclosed in CN105271399A, the "reduced titanium liquid" pre-feeding technology disclosed in CN107954471A, and the separate process of using Ti in the hydrochloric acid system disclosed in CN116081685A. 3+ A reducing atmosphere is required. However, the selective deep removal technology for vanadium, chromium, and manganese in sulfuric acid process titanium dioxide solutions has limitations. CN102627321A reduces impurities through freeze crystallization and composite flocculation, but it has poor selectivity for V, Cr, and Mn, and requires a large amount of flocculant. CN114671460B removes impurities in the metatitanic acid stage, but the timing is too late, and some impurities have already entered the crystal lattice. USP4288416 and USP4321236 disclose methods for separating V / Cr using trialkylamine extractants, but the solvent consumption is high, making it difficult to achieve large-scale application in the sulfuric acid process titanium dioxide industry. Existing wet coating routes (such as the zirconium-gallium-organosilicon system disclosed in CN103305033B) may introduce new impurity components.

[0005] Mesoporous silica (such as MCM-41 and SBA-15) has been widely used as an adsorbent carrier in water treatment. However, in strongly acidic (pH≤1), high titanium concentration (TiO2 180~220g / L), and strongly reduction-oxidation sensitive sulfuric acid titanium solution systems, there is currently a lack of targeted technical solutions for the chelation adsorption of colorimetric heavy metal ions. Furthermore, single chelating groups are difficult to achieve high selectivity in this system: aminophosphonic acid groups (such as IDA-MPA type -N(CH2PO3H2)2) are not suitable for the chelation adsorption of various transition metals (containing Cr). 3+ V 4+ Cu 2+ Ni 2+ Fe 2+ Fe 3+ (etc.) all have strong complexing ability; 8-hydroxyquinoline has a strong complexing ability against Cu 2+ / Ni 2+ / Zn 2+ / Fe 2+ The complexation constants of Mn are also relatively high. 2+ The complexation is relatively weak, therefore simple single-group modification pathways are difficult to implement in environments containing large amounts of Fe. 2+ Achieve efficient deep removal in complex titanium liquids with concentrations of 28~35 g / L.

[0006] In summary, the sulfuric acid process for titanium dioxide production requires a deep vanadium / chromium / manganese removal process that can be implemented in the titanium solution stage after leaching and reduction, without affecting subsequent hydrolysis processes, and that is simple, recyclable, and compatible with existing production lines. Summary of the Invention

[0007] The technical problems to be solved by this invention include: (1) the existing sulfuric acid process for titanium liquid purification has poor selectivity for V, Cr, and Mn, resulting in insufficient whiteness, decolorizing power, and color stability of the final product; (2) the existing coating route is prone to introducing new impurity components; (3) the amine extractant system suffers from large solvent loss and severe third phase formation, resulting in insufficient industrial adaptability; (4) mesoporous adsorbent materials modified with a single chelating group are not suitable for use in high concentrations of Fe. 2+ In a strong acid titanium solution system, it is difficult to achieve simultaneous, efficient, and deep removal of multiple impurities such as V, Cr, and Mn.

[0008] In the sulfuric acid process titanium liquid system, due to Ti 4+ Mainly TiO 2+ ·nSO4 2- The presence of sulfate groups (which occupy coordination sites on Ti as strong ligands, and the high H2SO4 concentration in the system leading to high sulfate activity) significantly suppresses coordination competition between Ti and the chelating groups immobilized within the pores. Simultaneously, this invention co-functionalizes aminomethylenephosphonic acid and 8-hydroxyquinoline groups on the same mesoporous pore wall, forming a multidentate spatial coordination field that enhances the coordination of V... 4+ Cr 3+ Mn 2+ The chromogenic heavy metal impurities achieve multi-mode synergistic chelation (phosphonic acid groups contribute oxygen donor coordination, quinoline groups contribute nitrogen-phenol oxygen donor coordination), and also affect Fe. 2+ The adsorption capacity of Fe is weak. 2+ The ferrous sulfate can be removed in a subsequent vacuum crystallization process without affecting the quality of the final product.

[0009] To solve the above-mentioned technical problems, the present invention provides the following three technical solutions: (i) an aminomethylenephosphonic acid / 8-hydroxyquinoline bifunctionalized mesoporous silica adsorbent (APO-MS); (ii) a method for preparing APO-MS; and (iii) a method for deep purification of vanadium, chromium, and manganese in sulfuric acid process titanium dioxide liquid using APO-MS.

[0010] To achieve the objective of this invention, the present invention first provides a method for deep purification of vanadium, chromium, and manganese in titanium dioxide produced by the sulfuric acid process, which includes the following steps:

[0011] A. Adjust the ORP potential of the titanium liquid to -150mV to -80mV;

[0012] B. The titanium liquid after being regulated in step A is purified by passing it through a multi-stage series adsorption device filled with bifunctional mesoporous silica adsorbent at 45~55℃ under inert gas protection.

[0013] The bifunctionalized mesoporous silica adsorbent was prepared by the following method:

[0014] a. Using tetraethyl orthosilicate as the silicon source, hexadecyltrimethylammonium bromide as the template agent, and water as the solvent, a hydrolysis-condensation reaction was carried out simultaneously at 35~45℃ and pH 10.5~11.5. After the reaction was completed, the mesoporous silica matrix was obtained by solid-liquid separation, washing, drying and calcination.

[0015] b. Disperse the mesoporous silica matrix in toluene, add γ-aminopropyltriethoxysilane, and control the molar ratio of silanol groups to γ-aminopropyltriethoxysilane in the mesoporous silica matrix to be 1:1.1~1.3. After reflux reaction, the mixture is separated into solid and liquid, washed and dried to obtain aminated mesoporous silica.

[0016] c. Aminated mesoporous silica was dispersed in an acidic medium with phosphorous acid and formaldehyde in a molar ratio of 1:2.5±0.1:3.0±0.1 and subjected to a Mannich reaction at 80~100℃. After solid-liquid separation, washing and drying, mesoporous silica with aminophosphonic acid functional groups was obtained.

[0017] d. The aminophosphonic acid functionalized mesoporous silica and 5-formyl-8-hydroxyquinoline were dispersed in an ethanol / water mixed solvent at a mass ratio of 8~12:1 and subjected to a condensation reaction at 55~65℃. Then, 1.2~2 times the molar amount of 5-formyl-8-hydroxyquinoline NaBH3CN was added and a reduction reaction was carried out at 35~45℃. After the reaction was completed, the mixture was separated into solid and liquid components, washed and dried to obtain the bifunctionalized mesoporous silica adsorbent.

[0018] In the above method, in step A, the titanium solution is the leaching titanium solution obtained after acid hydrolysis and iron filings reduction by sulfuric acid method.

[0019] In the above method, step A, the titanium liquid composition includes: TiO2 180~220 g / L, F value 1.85~1.95, Fe 2+ 28~35g / L, Ti 3+ 1.5~3.0g / L, V 20~150mg / L, Cr 20~150mg / L, Mn 50~250mg / L.

[0020] In the above method, in step A, the ORP is adjusted by adding iron powder slurry, and the concentration of the iron powder slurry is 0.5~2wt%. The iron powder slurry can be prepared by adding iron powder (particle size ≤45μm, purity ≥98%) to water or titanium liquid; using iron powder slurry, compared with directly adding iron powder, makes it easier to achieve precise addition and online closed-loop control of ORP.

[0021] In the above method, in step B, when passing through the adsorption device, the flow rate of the titanium liquid is 1.5~3.0 BV / h; preferably 1.5~2.5 BV / h.

[0022] In the above method, in step B, the packing density of the bifunctional mesoporous silica adsorbent in each segment is 300~500 kg / m³. 3 .

[0023] In the above method, in step B, the number of segments in series in the multi-segment adsorption device is 3 to 5.

[0024] In the above method, in step B, the multi-segment series adsorption device is made of 316L stainless steel lined with polytetrafluoroethylene.

[0025] In the above method, in step B, the purified titanium solution contains V≤10mg / L, Cr≤10mg / L, and Mn≤20mg / L.

[0026] Preferably, in step B of the above method, under the preferred process, the purified titanium liquid contains V≤5mg / L, Cr≤8mg / L, and Mn≤15mg / L.

[0027] The above method also includes step C, in which the bifunctional mesoporous silica adsorbent is regenerated by reverse desorption with an acidic reducing aqueous solution after adsorption saturation and then reused.

[0028] In the above method, in step C, the acidic reducing aqueous solution is a mixture of 3~8wt% H2SO4 + 0.5~2wt% ascorbic acid.

[0029] In the above method, in step C, the flow rate of reverse desorption is 0.5~2.0 BV / h, the time is 3~6h, and the desorption efficiency is ≥95%.

[0030] In the above method, in step C, after reverse desorption, the bifunctionalized mesoporous silica adsorbent is washed with water until the pH of the washing solution is ≥4 and then dried by nitrogen purging.

[0031] In the above method, in step a, the molar ratio of tetraethyl orthosilicate and hexadecyltrimethylammonium bromide is 1:4~4.5.

[0032] In the above method, in step a, the amount of water used is 3-4 L of water added for every 1 mol of tetraethyl orthosilicate.

[0033] In the above method, in step a, the hydrolysis-condensation reaction takes 15-25 hours.

[0034] In the above method, in step a, the calcination temperature is 500~600℃ and the time is 4~8h.

[0035] In the above method, in step a, the BET specific surface area of ​​the mesoporous silica substrate is ≥850m². 2 / g, pore size 3.0~4.0nm, pore volume ≥0.95cm³ 3 / g.

[0036] In the above method, in step b, the amount of toluene used is 0.8~1.2L of toluene per 100g of mesoporous silica matrix.

[0037] In the above method, the reflux reaction time in step b is 4~12h.

[0038] In the above method, step b involves drying at 100-120°C under vacuum for 2-6 hours.

[0039] In the above method, in step b, the amino grafting density of the aminated mesoporous silica is 2.0~2.8 mmol / g.

[0040] In the above method, in step c, the acidic medium is a 0.05~0.2mol / L hydrochloric acid aqueous solution.

[0041] In the above method, in step c, the amount of acidic medium used is 1.5~2.5L of acidic medium added per 100g of aminated mesoporous silicon.

[0042] In the above method, the reaction time in step c is 8~16h.

[0043] In the above method, step c involves drying at 100-120°C under vacuum for 4-8 hours.

[0044] In the above method, in step c, the reaction conversion rate is controlled to be 60-70%, so that 30-40% of unreacted amine groups are retained on the aminated mesoporous silica.

[0045] In the above method, in step d, the volume ratio of ethanol to water in the ethanol / water mixed solvent is 3~5:1.

[0046] In the above method, in step d, the amount of ethanol / water mixed solvent used is 0.8~1.2L of ethanol / water mixed solvent added per 100g of aminophosphonic acid functionalized mesoporous silica.

[0047] In the above method, the condensation reaction time in step d is 16~24h.

[0048] In the above method, the reduction reaction time in step d is 10~16h.

[0049] In the above method, step d involves drying under vacuum at 100-120°C for 4-8 hours.

[0050] In the above method, in step d, the BET specific surface area of ​​the bifunctional mesoporous silica adsorbent is ≥620 m². 2 / g, pore volume ≥0.65cm 3 / g, the density of aminomethylenephosphonic acid groups is 1.6~1.7mmol / g, and the loading of 8-hydroxyquinoline groups is 0.45~0.60mmol / g.

[0051] The present invention also provides a bifunctional mesoporous silica adsorbent, which is prepared by the above method.

[0052] This invention also provides the application of the above-mentioned bifunctional mesoporous silica adsorbent in the purification of titanium liquid.

[0053] The beneficial effects of this invention are:

[0054] (1) The present invention significantly improves the selectivity of impurity removal without affecting Ti 3+ Under the given concentration and F value conditions, deep synergistic removal of V, Cr, and Mn is achieved, with removal rates of over 80% for all three impurities (in the preferred embodiment, V / Cr / Mn removal rates are approximately 90% / 85% / 83%, respectively). This is significantly higher than conventional crystallization-reduction processes and single-group modified adsorbent schemes, and also achieves the removal of Fe. 2+ Highly selective rejection.

[0055] (2) The present invention can significantly improve the key properties of titanium dioxide. The rutile titanium dioxide produced has significantly improved whiteness, bleaching power and color stability under ultraviolet irradiation conditions compared with conventional process products, and the photochromic interconversion ΔE is significantly reduced.

[0056] (3) The adsorbent of the present invention has good stability in repeated use. The 8-hydroxyquinoline group is anchored to the inner wall of the pore in the form of secondary amine covalent bond, avoiding dissolution and loss in the strong acid titanium liquid system. The adsorption capacity retention rate of the typical adsorbent can still reach more than 80% after 80 cycles, which is significantly improved compared with the conventional physical impregnation loading method (which generally shows obvious loss after 10 to 20 cycles).

[0057] (4) The present invention has strong process integration. The multi-section fixed bed tower can be directly placed between the existing iron scrap reduction process and the vacuum crystallization process without major modifications to the main process; the operating temperature is mild (45~55℃) and the energy consumption is low.

[0058] (5) The present invention is environmentally friendly. V / Cr / Mn in the desorption liquid is recovered by neutralization-sulfidation precipitation. The by-products can be recycled as vanadium-chromium-manganese slag in vanadium-titanium metallurgy. The mesoporous silicon matrix can be alkali-melted and recycled at the end of its life cycle, resulting in a high resource utilization rate. Attached Figure Description

[0059] Figure 1 The image shows the FTIR spectrum of NH2-MS in Example 1.

[0060] Figure 2 For APO-MS-I in Example 1 31 P MAS NMR spectrum.

[0061] Figure 3 The above are the FTIR comparison spectra of APO-MS-I and NH2-MS in Example 1.

[0062] Figure 4 For APO-MS in Example 1 13 C CP / MAS NMR spectrum.

[0063] Figure 5 The image shows the FTIR comparison spectra before and after APO-MS reduction in Example 1.

[0064] Figure 6 The image shows the UV-Vis DRS spectrum of APO-MS in Example 1.

[0065] Figure 7 The image shows the XPS N 1s and O 1s high-resolution spectra of APO-MS in Example 1.

[0066] Figure 8 The images show the N2 adsorption-desorption isotherm and BJH pore size distribution of APO-MS in Example 1.

[0067] Figure 9 For example, APO-MS in Example 2 for V 4+ Cr 3+ Mn 2+ The isothermal adsorption curve.

[0068] Figure 10 The curve of adsorption capacity retention after multiple cycles of APO-MS in Example 2 is shown.

[0069] Figure 11 This is a comparison of the reflectance spectra of titanium dioxide from Example 2 and Comparative Example 1. Detailed Implementation

[0070] Specifically, the deep purification method for vanadium, chromium, and manganese in titanium dioxide solution using the sulfuric acid process of the present invention includes the following steps:

[0071] Step A: Titanium liquid pretreatment and potential control:

[0072] The leaching solution of titanium dioxide produced by the sulfuric acid process, after acidolysis and iron filings reduction (composition: TiO2 180~220g / L, F value 1.85~1.95, Fe...) is taken from the leaching solution of titanium dioxide produced by the sulfuric acid process. 2+ 28~35g / L, Ti 3+ 1.5~3.0 g / L, V 20~150 mg / L, Cr 20~150 mg / L, Mn 50~250 mg / L, pH < 1, online monitoring of redox potential (ORP, measured relative to an Ag / AgCl reference electrode). When the ORP is higher than -80 mV, 0.5~2 wt% iron powder slurry (particle size ≤ 45 μm) is automatically added to stabilize the ORP between -150 and -80 mV. This ORP range corresponds to Ti in the titanium melt. 3+ The reducing conditions, with a concentration of not less than 1.5 g / L, are intended to ensure V 4+ (VO) 2+ It is not oxidized to V by air contact surfaces or trace amounts of oxidizing species. 5+ (VO2) + ), and maintain Cr entirely as Cr 3+ The impurity exists in its original form. Potential control in this step plays a crucial role in stabilizing the impurity's form during the adsorption stage and is a prerequisite for achieving highly selective adsorption by APO-MS in subsequent steps.

[0073] Step B, multi-segment series adsorption:

[0074] The titanium liquid, after pretreatment and regulation in step A, is passed through a multi-stage (preferably 3-5 stages) series adsorption device (e.g., a multi-stage series fixed-bed adsorption tower) at a flow rate of 1.5-3.0 BV / h (bed volume / hour) (preferably 1.5-2.5 BV / h). Each tower (stage) is effectively filled with bifunctional mesoporous silica adsorbent with a bulk density of 300-500 kg / m³. 3 (That is, 300-500 kg of APO-MS adsorbent is filled per cubic meter, corresponding to a porosity of approximately 50-65%). The tower body is preferably made of 316L stainless steel lined with polytetrafluoroethylene (PTFE), with temperature controlled at 45-55℃ via a jacket, and covered with inert gases such as nitrogen throughout to prevent Ti from entering. 3+ V 4+ It is oxidized by air.

[0075] It should be noted that Fe coexists in the titanium liquid. 2+The concentration is relatively high (28~35 g / L), but this invention ensures effective removal of V / Cr / Mn target impurities through the synergistic effect of bifunctional groups and multi-segment tandem design, and also for Fe. 2+ The adsorption capacity of Fe is weak; 2+ In subsequent vacuum crystallization processes, Fe is separated and removed as ferrous sulfate, without affecting the quality of the final product. This invention utilizes APO-MS in a sulfuric acid process titanium liquid system (pH < 1, high H₂SO₄ concentration) to separate and remove Fe. 2+ The affinity for aminophosphonic acid groups in APO-MS is significantly lower than that for V. 4+ (VO) 2+ ) and Cr 3+ Fe 2+ It exists in large quantities as FeSO4 ion pairs, with effectively free Fe 2+ Low concentration, weak chelation driving force, although the N,O bidentate site of 8-hydroxyquinoline is effective against Fe 2+ It has some affinity, but under strongly acidic conditions (pH < 1), the protonation of quinoline nitrogen leads to a significant decrease in coordination ability, and Mn 2+ The complexation constant with 8-HQ under acidic conditions is much higher than that with Fe. 2+ Meanwhile, the multi-segment series design enables V 4 + / Cr 3+ Preferentially occupying high-affinity sites, Fe 2+ It is at a disadvantage in competitive adsorption, therefore it is less effective against Fe. 2+ Its adsorption capacity is weak.

[0076] After purification, the titanium solution should contain V ≤ 10 mg / L, Cr ≤ 10 mg / L, and Mn ≤ 20 mg / L, preferably V ≤ 5 mg / L, Cr ≤ 8 mg / L, and Mn ≤ 15 mg / L. Online ICP-MS monitoring can be performed at the end of each section every 30 minutes. If the threshold is exceeded for three consecutive times, the adsorbent in that section is considered saturated.

[0077] Step C: Adsorbent desorption and regeneration:

[0078] Adsorption-saturated APO-MS can be prepared using a mixture of 3-8 wt% (preferably 5 wt%) H2SO4 + 0.5-2 wt% (preferably 1 wt%) ascorbic acid (H2SO4 concentration range 3-8 wt%) to ensure the target ion (V 4+ / Cr 3+ / Mn 2+ Effective elution of V (ascorbic acid) is achieved, with ascorbic acid acting as a co-reducing agent to maintain a reducing environment in the eluent and prevent V from being absorbed during desorption. 4+ Oxidized by air to V 5+The desorption efficiency is ≥95%, achieved by altering the interaction strength between the desorbent and the adsorbent (preferably 1.0 BV / h) and reverse-flowing for 3-6 hours (preferably 4 hours). The desorption solution (containing V / Cr / Mn and a small amount of Fe) is subsequently treated as follows: first, neutralize to pH 8-10 with lime milk (or NaOH solution) to allow Fe to... 3+ / Fe 2+ Cr 3+ V (in the form of V₂O₅ or vanadate) is precipitated; then Na₂S is added to further precipitate the remaining Mn. 2+ The resulting composite precipitate is MnS (stable under pH > 4 conditions). After filtration, washing, and drying, it is converted into a V / Cr / Mn-containing by-product slag, which can be sent to vanadium-titanium metallurgy for comprehensive utilization. After reverse desorption, the bifunctionalized mesoporous silica adsorbent is washed with water until the washing solution pH ≥ 4 and then purged with nitrogen and dried before reuse.

[0079] Step D: Purify the titanium liquid and output it.

[0080] Purified titanium solution after multi-stage adsorption (composition: TiO2 concentration 185~222g / L, V≤5mg / L, Cr≤8mg / L, Mn≤15mg / L, Fe 2+ Ti 3+ (Basically unchanged) It can directly enter the subsequent conventional sulfuric acid process processes such as vacuum crystallization separation of ferrous sulfate, hydrolysis, salt treatment, and calcination, without the need for other modifications to the main process.

[0081] The present invention will be explained below with reference to embodiments. Those skilled in the art will understand that the following embodiments are for illustrative purposes only and should not be considered as limiting the scope of the invention. Where specific techniques or conditions are not specified in the embodiments, they shall be performed in accordance with the techniques or conditions described in the literature in the art or in accordance with the product manual.

[0082] The starting compounds, raw materials and / or reagents used in the reactions described in this invention can be obtained through legitimate commercial channels, or prepared by methods reported in chemical literature, or prepared according to organic synthesis techniques known to those skilled in the art.

[0083] Example 1: Preparation of bifunctionalized mesoporous silica adsorbent (APO-MS)

[0084] (a) Using tetraethyl orthosilicate (TEOS) as the silicon source and hexadecyltrimethylammonium bromide (CTAB) as the template agent, TEOS and CTAB were dissolved in deionized water at a molar ratio of 1:4.3 (3.5 L of deionized water for every 1 mol of TEOS). The pH was adjusted to 11.0 with ammonia water. The hydrolysis and polycondensation reaction were carried out simultaneously in a water bath at 40 °C with stirring for 20 h. After the reaction was completed, the mixture was filtered, and the white solid was washed three times each with deionized water and ethanol. After drying at 100 °C for 12 h, it was transferred to a muffle furnace and heated to 550 °C at a heating rate of 2 °C / min. The mixture was calcined in air for 6 h to remove the template agent CTAB. After natural cooling, the mixture was ground to obtain the mesoporous silica matrix (MS). MS was used to determine the BET specific surface area using the N2 adsorption-desorption isotherm (77K), the total pore volume was determined using the single-point method with P / P0≈0.99, and the main pore diameter was determined by fitting the BJH desorption branch. Small-angle X-ray diffraction (SAXS / low-angle XRD) showed diffraction peaks with ordered arrangement of mesopores at 2θ=2.0°~2.5°. Transmission electron microscopy (TEM) revealed a regular hexagonal mesopore array, as detailed in Table 1.

[0085] Table 1 Physical characterization data of mesoporous silica matrix (MS)

[0086]

[0087] (b) MS was dispersed in anhydrous toluene at a ratio of 100 g: 1 L to ensure that the solid was fully dispersed and suspended. γ-aminopropyltriethoxysilane (KH-550) was added to KH-550 at a molar ratio of 1:1.2 to the silanol groups on the MS surface (determined by thermogravimetric analysis (TGA, N2 atmosphere, 25→800℃, 10℃ / min), combined with solid 29Si MAS NMR (Q3 peak δ≈-101ppm, corresponding to Si(OSi)3OH), the density of silanol groups in this batch of MS was approximately 3.8 mmol / g). The mixture was refluxed at 80℃ for 8 h, filtered, washed with toluene, and then vacuum dried at 120℃ for 4 h to obtain aminated mesoporous silica (NH2-MS). The amino grafting density in NH2-MS was determined to be 2.42±0.18 mmol / g.

[0088] The amino grafting density was comprehensively quantified using the following four methods: (i) The nitrogen content in NH2-MS was determined using a CHNS elemental analyzer, and the amino density was calculated accordingly; (ii) Thermogravimetric analysis (TGA, N2 atmosphere, heating to 800℃ at 10℃ / min) was used, and the weight loss of the aminated product in the 200~600℃ range corresponded to the thermal decomposition of the propylamino side chain. Based on the weight loss rate, the grafting density was calculated according to KH-550 residue 73; (iii) Ninhydrin colorimetric method: a certain amount of NH2-MS was added to 1.0% ninhydrin ethanol solution, and the mixture was subjected to color development in a boiling water bath for 15 min. The absorbance was measured at 570 nm, and the free primary amino groups were quantified using a glycine standard curve; (iv) Fourier transform infrared spectroscopy (FTIR, KBr pellet method): 3450 cm⁻¹ -1 The broad absorption corresponds to the adsorption of ν(OH) water and surface silanol groups); 3380 cm -1 The vibration at this point is the stretching vibration of amino ν(NH), 1565 cm⁻¹ -1 The corresponding δ(NH) bending vibration is located at 2935 cm. -1 With 2870cm -1 The position represents the ν(CH) vibration of the aminopropyl side chain; 1640 cm⁻¹ -1 The area is a water-adsorbed HOH bend; 1080cm -1 (Strong, Wide) is ν as (Si-O-Si), 800cm -1 The location is symmetrical ν s (Si-O-Si), 470cm -1 The value at δ(Si-O-Si) is 960 cm. -1 The presence of characteristic peaks for ν(Si-OH), NH, and CH at this location proves that the γ-aminopropyl group has been successfully grafted onto the surface of the mesoporous silica substrate; the results are shown in Table 2 and... Figure 1 .

[0089] Table 2. NH2-MS characterization data of aminated mesoporous silica

[0090]

[0091] (c) Take NH2-MS and phosphorous acid (H3PO3) and formaldehyde (HCHO) at a molar ratio of 1:2.5:3.0 (NH2-MS is based on the molar amount of amino groups) and disperse them in 0.1 mol / L hydrochloric acid medium (add 2 L of 0.1 mol / L hydrochloric acid aqueous solution for every 100 g of NH2-MS). Ensure that the solid is completely dispersed and reacts in the acidic medium (H3PO3 and HCHO are both soluble in this aqueous solution). React at 90 °C for 12 h (Mannich reaction) to convert some amino groups into aminomethylenephosphonic acid groups -NHCH2PO3H2 or -N(CH2PO3H2)2. After the reaction is completed, filter the reaction mixture, wash the solid product with deionized water until the pH of the filtrate is ≥4, wash it once with ethanol, and dry it under vacuum at 120 °C for 6 h to obtain aminophosphonic acid functionalized mesoporous silica (APO-MS-Ⅰ). This step, by controlling the combination of reaction time, temperature, and substrate molar ratio, aims to achieve a Mannich reaction conversion of 60–70% (conversion based on the amount of NH2 involved in the Mannich reaction). This means that approximately 30–40% of unreacted primary amine groups are retained on the NH2-MS, serving as reaction sites for the subsequent condensation reaction with aldehydes. The reaction conversion can be determined by titration of residual H3PO3 in the reaction solution (iodometric method) or by examining the solid phase of the product. 31 Confirmed by a combination of P NMR and elemental analysis (C / N / P).

[0092] In this invention, the Kabachnik-Fields / Mannich reaction cascade mechanism based on -NH2 + H3PO3 + HCHO actually proceeds in two steps: the first step generates the monosubstituted product -NHCH2PO3H2 (mono-Mannich), and the second step involves the secondary amine NH of this monosubstituted product reacting further with HCHO / H3PO3 to generate the disubstituted product -N(CH2PO3H2)2 (di-Mannich). According to the reactivity order in organic chemistry, the primary amine (NH2) has a higher nucleophilicity than the secondary amine (-NHCH2PO3H2), and since the NH atom on the nitrogen of the disubstituted product (tertiary amine) is no longer present, the reaction cannot continue. Therefore, under the controlled reaction conditions of 12 h, 90 °C, and a molar ratio of 1:2.5:3.0, the reaction system of this invention actually exhibits a cascade process of "primary amine preferential reaction—first conversion to monosubstituted—further conversion to disubstituted." Thus, the amine species in APO-MS-I are actually a mixture of three types: disubstituted -N(CH2PO3H2)2: approximately 35~45% (approximately 42%), providing the main V... 4+ / Cr 3+Multidentate chelating coordination field; monosubstituted -NHCH2PO3H2: about 15~25% (about 22% secondary amine), providing adsorption sites; unreacted -NH2: about 30~40% (about 36% primary amine), which can condense with the aldehyde group in step (d). The mixed morphology of the present invention does not affect the performance of the adsorbent of the present invention: (i) the disubstituted group provides the main multidentate chelating sites, for V 4+ Cr 3+ (ii) The phosphonic acid oxygen and secondary amine N of the monosubstituted group can still contribute auxiliary coordination to the metal ion; (iii) The -NH2 site is the reaction site introduced by the subsequent 8-hydroxyquinoline.

[0093] Detection method: (i) 31 P-Solid Magic Angle Rotation Nuclear Magnetic Resonance (P-Solid Magic Angle Rotation Nuclear Magn 31 P MAS NMR (MAS rotation speed 10 kHz): A chemical shift peak of -P(O)(OH)2 appears at δ≈6~9 ppm; by quantitative integration comparison with disodium hydrogen phosphate standard, the total molar content of P element in the adsorbent can be determined, see [reference]. Figure 2 The main resonance peak is centered in the range of δ≈6~9ppm, corresponding to the chemical shift of -P(O)(OH)2. The peaks are asymmetric and can be decomposed into two chemical environments by Voigt function peak fitting: the strong peak at δ≈7.5ppm belongs to phosphonic acid P in disubstituted -N(CH2PO3H2)2, and the weaker peak at δ≈5.8ppm belongs to phosphonic acid P in monosubstituted -NHCH2PO3H2. The integral area ratio of the two peaks is about 1.9:1, which proves that disubstituted and monosubstituted groups coexist in APO-MS-I and that disubstituted groups are the main species. The weak signals at δ≈25ppm and -10ppm are rotor sidebands (SSBs). It can be seen that the product of this invention is a di / monosubstituted mixed system.

[0094] (ii) The residual H3PO3 in the reaction solution was determined by iodometric titration: a certain volume of the reaction solution was acidified with KI and dilute H2SO4, and then titrated with standard I2 solution until it turned blue (starch indicator). The amount of residual H3PO3 was calculated from the amount of I2 consumed according to the reaction H3PO3 + I2 + H2O → H3PO4 + 2HI. Combined with the initial feed of the reaction, the total conversion rate of the Mannich reaction can be calculated to be 62~68% (64.3%), as shown in Table 3.

[0095] (iii) C and N elements were determined using a CHN elemental analyzer for the solid product, and P element was determined using ICP-OES (samples before and after digestion). Based on the theoretical model, the molar ratios of the three types of groups were deduced using the following equations: [Total N] = [-NH2] + [-NHCH2PO3H2] + [-N(CH2PO3H2)2], [Total P] = [-NHCH2PO3H2] + 2×[-N(CH2PO3H2)2]. [Total N] is derived from the values ​​measured in step (b), and [Total P] is determined by ICP-OES. The mono-substituted / di-substituted ratio is determined by… 31 The high-field and low-field chemical shift peak integration ratio of P NMR was used for confirmation. The APO-MS-I measured values ​​were: C 11.8 wt%, N 2.65 wt%, P 5.62 wt%, as shown in Table 3.

[0096] (iv) FTIR spectra are shown in Figure 3 Compared with NH2-MS, three new groups of characteristic vibrational peaks of phosphonic acid groups appeared in the APO-MS-I spectrum: 950 cm⁻¹ -1 Vibration at ν (P=O); 1140cm -1 Nearby ν(PO) vibration; 1200cm -1 The ν(P-OH) vibration at 2700 cm⁻¹; furthermore, at 2700 cm⁻¹ -1 A broad band of P-OH hydrogen bonding appears nearby, and at 3380 cm⁻¹ -1 The intensity of the ν(NH) peak at 1565 cm⁻¹ is significantly weaker than that of NH₂-MS. -1 The δ(NH) peak at that position also weakened accordingly, indicating that some amino groups had been converted to the -NHCH2PO3H2 structure via the Mannich reaction; however, the residual NH signal could still be observed, compared to... 31 The P NMR and elemental analysis data are in agreement, confirming that the product is a mixed system of disubstituted / monosubstituted / unreacted amines.

[0097] Table 3. Ratio of three types of amine groups in APO-MS-I and conversion rate in the Mannich reaction.

[0098]

[0099] (d) Disperse APO-MS-I and 5-formyl-8-hydroxyquinoline at a mass ratio of 10:1 (i.e., the molar ratio of residual -NH2 in APO-MS-I to the aldehyde group in 5-formyl-8-hydroxyquinoline is approximately 1.2:1, and -NH2 in APO-MS-I accounts for approximately 36%, approximately 0.68 mmol / g), in a mixed solvent of ethanol / water at pH 4.5 (V / V 4:1, 1L of ethanol / water mixed solvent added per 100g APO-MS-I). Perform a condensation reaction at 60℃ for 18h. The residual amine group undergoes a Schiff base condensation reaction with the aldehyde group of 5-formyl-8-hydroxyquinoline (-NH2 + OHC-Q → -N=CH-Q + H2O), forming a covalent imine bond. Maintain the pH of the reaction solution at 4.5 (acetic acid / sodium acetate buffer, 0.1mol / L, pH...). 4.5), then NaBH3CN (added at 1.5 times the molar amount of 5-formyl-8-hydroxyquinoline) was added to the ethanol medium, and the concentration was confirmed by online FTIR monitoring at 1655 cm⁻¹. -1 The complete disappearance of the C=N stretching vibration peak marked the reduction endpoint. The reaction was carried out at 40℃ for 12 hours, resulting in complete reaction. The imine exhibited a more stable structure (-N=CH-Q + 2[H] → -NH-CH2-Q, where Q is an 8-hydroxyquinoline ring), thus covalently anchoring the 8-hydroxyquinoline group to the inner wall of the pores. This covalent bonding method significantly improved the stability and cycle life of the 8-hydroxyquinoline group in a strongly acidic titanium liquid system compared to physical impregnation / hydrogen bonding. After the reaction was complete, the solid was filtered and washed three times each with ethanol and deionized water, and then vacuum dried at 120℃ for 6 hours. The resulting adsorbent was designated APO-MS, which simultaneously loaded aminomethylenephosphonic acid and 8-hydroxyquinoline.

[0100] In this step, the residual amine group on the matrix side (the unreacted primary amine -NH2 in step (c)) undergoes a condensation reaction with the aldehyde group (-CHO, attached to the 5-position of the quinoline ring) of 5-formyl-8-hydroxyquinoline to form a Schiff base (C=N). Then, the C=N is selectively reduced to a CN single bond by NaBH3CN, and the resulting covalent connection is a secondary amine type -NH-CH2-Q, where N: nitrogen atom from the amino group on the matrix side (grafted to the end of the silanol / propyl chain); -CH2-: reduction product from the aldehyde carbon of 5-formyl-8-hydroxyquinoline (-CHO → -CH2-); Q: 8-hydroxyquinoline ring, connected to -CH2- through the 5-position of the ring, and the free phenolic hydroxyl group (-OH) is retained at the 8-position of the ring, which together with the quinoline nitrogen at the 1-position constitutes an N,O bidentate coordination unit.

[0101] Structural characterization: (i) 13 C solid CP / MAS NMR: see Figure 4The peaks at δ≈10ppm represent the Si-CH2 terminal carbon; at δ≈24ppm, the aminopropyl intermediate methylene-CH2-; at δ≈45ppm, the -CH2-N terminal carbon; and at δ≈51ppm, the -N-CH2-Ar methylene, demonstrating that 8-hydroxyquinoline is covalently anchored; the peak at δ≈60ppm represents the P-CH2-N methylene introduced by the Mannich reaction; seven characteristic peaks appear in the aromatic region within the range of δ≈110~155ppm, which are attributed to the nine sps of the 8-hydroxyquinoline ring. 2 No C=N signal was observed at δ≈165ppm, indicating that the Schiff base intermediate was reduced to a more stable CNH structure in the NaBH3CN reduction step of step (d). Figure 5 The FTIR spectra are stable;

[0102] (ii) FTIR: see Figure 5 The original spectrum was displayed at 1655 cm⁻¹. -1 A strong ν(C=N) vibrational peak appears at 3300-3450 cm⁻¹, indicating that Schiff base condensation has occurred to form an imine intermediate; after reduction with NaBH₃CN, the ν(C=N) peak completely disappears, and a new peak appears at 3300-3450 cm⁻¹. -1 The significantly enhanced ν(NH) stretching vibration peak in the region proves that C=N has been reduced to C-NH. This comparison demonstrates that the imine (C=N) has been reduced by NaBH3CN to a more stable covalent structure (C-NH). In the final product APO-MS, the 8-hydroxyquinoline group is anchored by -NH-CH2- linkage, rather than existing in the form of an imine (imines are easily hydrolyzed in strongly acidic titanium solutions, while secondary amines are stable).

[0103] (iii) Ultraviolet-Vis DRS: see Figure 6 The APO-MS spectrum, compared to NH2-MS, exhibits two distinct characteristic absorption bands: a strong band at 240 nm, representing the π→π* transition of the quinoline ring; and a relatively broad absorption band from 320 to 350 nm (centered at approximately 335 nm), representing the superposition of the n→π* transition of 8-hydroxyquinoline and the intramolecular charge transfer (ICT) transition of the phenolic hydroxy-quinoline nitrogen. These two characteristic absorption bands indicate that the 8-hydroxyquinoline group has been successfully introduced into the adsorbent surface. No strong absorption was observed near 400 nm, indicating the absence of 8-hydroxyquinoline or imine residues. Therefore, this invention successfully prepared APO-MS.

[0104] ( XPS N 1s and O 1s high-resolution spectra: see Figure 7 The N 1s spectrum shows three components: a quinoline ring pyridine nitrogen with high electron density at 398.6 eV, a secondary amine nitrogen (-NH-CH2-Q) with a main peak at 399.5 eV, and a small amount of protonated nitrogen at 400.6 eV.+ (This is due to water adsorption in a strong acid environment or the presence of charged components during testing). The integral area of ​​the secondary amine component (399.5 eV) is significantly larger than that of the quinoline component (398.6 eV), consistent with the -NH-CH2-Q structure obtained by the condensation and reduction of residual amine and 8-HQ aldehyde groups. The O1s spectrum shows three components: the main peak at 530.5 eV corresponds to the oxygen in the Si-O-Si framework (the adsorbent host); the peak at 532.3 eV is the hydroxyl oxygen in 8-hydroxyquinoline phenol; and the peak at 533.0 eV is the oxygen in the P-OH of phosphonic acid, further demonstrating the simultaneous presence of bifunctionalized groups on the adsorbent surface.

[0105] APO-MS adsorbent performance characterization:

[0106] (i) BET specific surface area and pore volume: Micromeritics ASAP 2460 fully automated specific surface area and pore size analyzer, APO-MS, degassed at 120℃ under vacuum (<5μmHg) for 12h, and the N2 adsorption-desorption isotherm was measured at 77K (liquid nitrogen bath). The results are shown in […]. Figure 8 This indicates that the channel is a regular columnar mesopore, S BET 648m 2 / g, total pore volume V P It is 0.72cm 3 / g, pore size distribution is unimodal and narrow, main pore size D p The wavelength was 3.6 nm, slightly smaller than the 3.8 nm of the substrate MS, and the full width at half maximum (FWHM) was <1.0 nm, indicating that the functional grafting did not destroy the ordered mesoporous structure.

[0107] (ii) Density of aminomethylenephosphonic acid groups: The total phosphorus content in the adsorbent digestion solution was determined by ICP-OES, combined with... 31 The quantitative integration of PMAS NMR was performed using standard samples, and the group density was calculated based on the equivalent -N(CH2PO3H2)2. The aminomethylenephosphonic acid group density in APO-MS was 1.64 mmol / g.

[0108] (iii) Loading of 8-hydroxyquinoline group: The loading of 8-hydroxyquinoline group in APO-MS was 0.52 mmol / g by dual quantification using UV-Vis standard curve method (the adsorbent was ultrasonically dissociated in NaOH / EDTA solution, and the absorbance was measured at 240 nm, and quantification was performed using 8-hydroxyquinoline standard as a standard curve) and N content increment method in CHN elemental analysis.

[0109] (iv) TGA: In N2 atmosphere, the temperature is increased to 800℃ at 10℃ / min, and the total weight loss in the 200~600℃ range is 18~22wt%.

[0110] Example 2

[0111] The titanium solution was taken from the leaching solution after acidolysis and iron filings reduction of a medium-sized sulfuric acid process titanium dioxide production line in China. Its main components are: TiO2 198g / L, F value 1.92, Fe 2+ 31.5g / L, Ti 3+ 2.4g / L, V (as VO) 2+ (Calculated) 38mg / L, Cr (as Cr) 3+ (Calculated) 41mg / L, Mn (as Mn) 2+ (Total) 78 mg / L, density 1.52 g / cm³ 3 .

[0112] Step 1: Place the above titanium liquid in a sealed adsorption vessel, and adjust it to -115mV using the ORP online controller (iron powder slurry concentration is 0.6wt%). 4+ (VO) 2+ ) form, Cr in Cr 3+ Form, Mn with Mn 2+ It exists in the form of a liquid at 50℃ under nitrogen protection. The preparation method of the iron powder slurry is as follows: industrial grade iron powder (particle size ≤45μm, purity ≥98%, i.e., iron powder above 325 mesh) is mixed with titanium liquid (or deionized water) at a ratio of 0.5~2wt% to form a suspension. The suspension is continuously stirred in a sealed storage tank under nitrogen protection (to prevent iron powder from settling and being oxidized by air), and automatically added to the titanium liquid by a peristaltic pump.

[0113] Step 2: The titanium liquid is passed through a three-stage series fixed-bed adsorption tower at a flow rate of 2.0 BV / h (each stage is filled with APO-MS prepared in Example 1, and the packing density of each stage is 380 kg / m³). 3 (Tower diameter φ300mm, bed height 1500mm, net weight of adsorbent per section approximately 40kg).

[0114] Step 3: Samples were taken every 30 minutes to determine V, Cr, and Mn using online ICP-MS. After 8 hours of operation, the effluent composition was: TiO2 196.5 g / L, Fe... 2+ 31.0g / L, Ti 3+ The removal rates of the three target impurities were 2.2 g / L, V 3.8 mg / L, Cr 6.1 mg / L, and Mn 13.2 mg / L, respectively: V 90.0%, Cr 85.1%, and Mn 83.1%. APO-MS showed that the removal rates of V... 4+ Cr 3+ Mn 2+ The isothermal adsorption curves are shown below. Figure 9 ;

[0115] Step 4: The purified titanium solution is subjected to conventional vacuum crystallization (-25℃) to separate ferrous sulfate, concentrated to 210 g / L with a thin film, and hydrolyzed with rutile seed crystals (0.7 wt%). 50=925nm), bleaching, salt treatment (K:P:Zn:Al = 0.30:0.18:0.10:0.32wt%), calcination (gradient heating 650→880→960℃, hold for 8h), wet milling, coating, organic treatment, and vapor jet pulverization were performed to obtain rutile titanium dioxide finished product, the properties of which are shown in Table 4;

[0116] Step 5: After APO-MS adsorption saturation, reverse desorption was performed for 4 hours using a mixed acidic reducing aqueous solution of 5wt% H2SO4 + 1wt% ascorbic acid at a flow rate of 1.0 BV / h. The desorption efficiency was ≥95%. The solution was then washed with deionized water until the pH of the washing solution was ≥4, and then purged with nitrogen and dried. The solution was then regenerated for reuse. The adsorption capacity retention curves of APO-MS after multiple cycles are shown in [Figure number missing]. Figure 10 .

[0117] Table 4. Performance of titanium dioxide in Example 1

[0118]

[0119] Example 3

[0120] The ORP was adjusted to -130mV and the temperature was 55℃; the adsorption flow rate was increased to 3.0 BV / h, and the number of tower layers was increased from 3 to 4. The other conditions were the same as in Example 2.

[0121] The purified titanium solution contained V 4.6 mg / L, Cr 7.5 mg / L, and Mn 14.8 mg / L, with removal rates of V 87.9%, Cr 81.7%, and Mn 81.0%, respectively. The titanium dioxide performance was as follows: whiteness 99.0, tinting strength 1828, volatile matter at 105℃ 0.34%, gloss retention rate after 1000h QUV 86.2%, and ΔE 0.55. This indicates that good quality can be maintained even with increased production capacity.

[0122] Example 4

[0123] The titanium solution was replaced with a high-vanadium, chromium, and manganese titanium solution with the following impurity content: V 92 mg / L, Cr 95 mg / L, Mn 165 mg / L, ORP-120 mV, temperature 50℃, flow rate 1.5 BV / h, 5 stages in series, and the APO-MS packing density increased to 450 kg / m³. 3 The remaining conditions are the same as in Example 2.

[0124] The purified titanium solution contained V 8.2 mg / L, Cr 9.0 mg / L, and Mn 18.5 mg / L, with removal rates of V 91.1%, Cr 90.5%, and Mn 88.8%, respectively. The titanium dioxide performance was as follows: whiteness 98.6, tinting strength 1810, ΔE 0.70, and gloss retention rate of 84.8% after 1000 hours of QUV testing. This demonstrates that the present invention is also applicable to titanium solutions with high impurities.

[0125] Comparative Example 1

[0126] Without using APO-MS adsorption purification, titanium dioxide solution (V 38 mg / L, Cr 41 mg / L, Mn 78 mg / L) was directly subjected to vacuum crystallization + hydrolysis + salt treatment + calcination + coating. The resulting titanium dioxide properties were: TiO2 93.5%, whiteness 97.4, tinting strength 1718, volatile matter at 105℃ 0.48%, oil absorption 22.3 g / 100 g, resistivity 82 Ω·m, UV 100h ΔE 1.62, QUV 1000h gloss retention 64.1%, and dispersibility grade 5.5. A comparison of the reflectance spectra of the titanium dioxide from Example 2 and Comparative Example 1 is shown in the figure. Figure 11 .

[0127] Comparative Example 2

[0128] Titanium solution (V 38 mg / L, Cr 41 mg / L, Mn 78 mg / L) was extracted once with 5 vol% trialkylamine-kerosene solvent (O / A=1:2, 60℃, 10 min).

[0129] The purified titanium solution contained V 18 mg / L and Cr 22 mg / L, with removal rates of 53% and 46% respectively. Mn was not removed at all (76 mg / L), and a third phase was formed in the extractant. The titanium dioxide performance was as follows: whiteness 98.0, tinting strength 1755, and ΔE 1.20. The kerosene solvent was introduced into the hydrolysis process, resulting in large fluctuations in the D50 of metatitanic acid (approximately ±18%).

[0130] Comparative Example 3

[0131] Unfunctionalized mesoporous silica matrix (MS) was used as the adsorbent, and the other conditions were the same as in Example 2.

[0132] The purified titanium solution contained 30 mg / L V, 35 mg / L Cr, and 65 mg / L Mn, with removal rates of 21%, 15%, and 17%, respectively. This indicates that mesoporous silica itself has limited adsorption capacity for target impurities when there are no functional groups, and the main adsorption effect comes only from the weak physical adsorption of silanol groups.

[0133] Comparative Example 4

[0134] Unfunctionalized aminophosphonic acid-functionalized mesoporous silica (APO-MS-I) was used as the adsorbent, and the other conditions were the same as in Example 2.

[0135] Purified titanium liquid: Fe 2+The removal rates of V (24.3 g / L), V (5.2 mg / L), Cr (7.0 mg / L), and Mn (48 mg / L) were 22.9%, 86.3%, 82.9%, and 38.5%, respectively. Titanium dioxide properties: whiteness 98.4, tinting strength 1782, ΔE 0.95, and QUV 1000h gloss retention 78.2%. This indicates that the aminomethylene phosphonic acid group has a significant effect on the removal of V... 4+ Cr 3+ It has good complexing-adsorption capacity (its phosphate oxygen donor and V 4+ Cr 3+ (forming stable chelates), but for Mn 2+ It has relatively weak adsorption capacity, but exhibits a significant chelating ability for iron.

[0136] Comparative Example 5

[0137] The adsorbent was directly condensed and reduced with 5-formyl-8-hydroxyquinoline using NH2-MS (without the Mannich reaction to introduce an aminomethylenephosphonic acid group), and the other conditions were the same as in Example 2.

[0138] Purified titanium liquid: Fe 2+ The removal rates of 26.8 g / L of magnesium oxide, 25 mg / L of vitamin C, 31 mg / L of chromium oxide, and 16 mg / L of manganese oxide were 14.9%, 34.2%, 24.4%, and 79.5%, respectively. Titanium dioxide properties included whiteness of 97.9, tinting strength of 1740, ΔE of 1.32, and a gloss retention rate of 71.0% after 1000 hours of QUV testing. This indicates that the 8-hydroxyquinoline group has a significant effect on the removal of manganese oxides (Mn). 2+ It forms an N,O-bidentate coordination complex, exhibiting good adsorption performance, but its adsorption of V in solution is limited. 4+ Cr 3+ Its capture ability is limited, and it has a certain adsorption capacity for iron.

[0139] Based on Examples 1-3 and Comparative Examples 4-5, it can be seen that the aminomethylenephosphonic acid functionalized adsorbent alone has a significant effect on V 4+ Cr 3 + It exhibits good adsorption capacity, but not for Mn 2+ Weaker, 8-hydroxyquinoline-functionalized adsorbents alone are less effective against Mn 2+ Performed well, but for V 4+ Cr 3+ Weaker; the synergistic bifunctional adsorbent (APO-MS) simultaneously anchors two types of chelating groups through the inner wall of the pores, forming a synergistic spatial coordination field, which can not only remove V but also... 4+ Cr 3+ Mn 2+Furthermore, it further improves the removal effect, enabling deep removal of all three impurities (removal rate V≥85%, Cr≥81%, Mn≥81%, with preferred removal rate V≥90%, Cr≥85%, Mn≥83%), and the final titanium dioxide performance indicators (whiteness, tinting strength, ΔE, QUV gloss retention rate) are significantly better than those of the single-function solution.

Claims

1. A method for deep purification of vanadium, chromium, and manganese in titanium dioxide produced by the sulfuric acid process, characterized in that: Includes the following steps: A. Adjust the ORP potential of the titanium liquid to -150mV to -80mV; B. The titanium liquid after being regulated in step A is purified by passing it through a multi-stage series adsorption device filled with bifunctional mesoporous silica adsorbent at 45~55℃ under inert gas protection. The bifunctionalized mesoporous silica adsorbent was prepared by the following method: a. Using tetraethyl orthosilicate as the silicon source, hexadecyltrimethylammonium bromide as the template agent, and water as the solvent, a hydrolysis-condensation reaction was carried out simultaneously at 35-45℃ and pH 10.5-11.

5. After the reaction was completed, the mesoporous silica matrix was obtained by solid-liquid separation, washing, drying and calcination. b. Disperse the mesoporous silica matrix in toluene, add γ-aminopropyltriethoxysilane, and control the molar ratio of silanol groups to γ-aminopropyltriethoxysilane in the mesoporous silica matrix to be 1:1.1~1.

3. After reflux reaction, the mixture is separated into solid and liquid, washed and dried to obtain aminated mesoporous silica. c. Aminated mesoporous silica was dispersed in an acidic medium with phosphorous acid and formaldehyde in a molar ratio of 1:2.5±0.1:3.0±0.1 and subjected to a Mannich reaction at 80~100℃. After solid-liquid separation, washing and drying, mesoporous silica with aminophosphonic acid functional groups was obtained. d. The aminophosphonic acid functionalized mesoporous silica and 5-formyl-8-hydroxyquinoline were dispersed in an ethanol / water mixed solvent at a mass ratio of 8~12:1 and subjected to a condensation reaction at 55~65℃. Then, 1.2~2 times the molar amount of 5-formyl-8-hydroxyquinoline NaBH3CN was added and a reduction reaction was carried out at 35~45℃. After the reaction was completed, the mixture was separated into solid and liquid components, washed and dried to obtain the bifunctionalized mesoporous silica adsorbent.

2. The method for deep purification of titanium dioxide, titanium liquid, vanadium, chromium, and manganese using the sulfuric acid process according to claim 1, characterized in that: At least one of the following must be met: In step A, the titanium solution is the leaching titanium solution obtained after acid hydrolysis and iron filings reduction using the sulfuric acid method; In step A, the titanium liquid composition includes: TiO2 180~220 g / L, F value 1.85~1.95, Fe 2+ 28~35g / L, Ti 3+ 1.5~3.0g / L, V 20~150mg / L, Cr 20~150mg / L, Mn 50~250mg / L; In step A, the ORP is adjusted by adding iron powder slurry, with the concentration of the iron powder slurry being 0.5~2wt%.

3. The method for deep purification of vanadium, chromium, and manganese in titanium dioxide solution using the sulfuric acid process according to claim 1, characterized in that: At least one of the following must be met: In step B, the flow rate of the titanium liquid through the adsorption device is 1.5~3.0 BV / h; preferably 1.5~2.5 BV / h. In step B, the packing density of the bifunctional mesoporous silica adsorbent in each section is 300~500 kg / m³. 3 ; In step B, the number of segments in the series adsorption device is 3 to 5. In step B, the multi-stage series adsorption device is made of 316L stainless steel lined with polytetrafluoroethylene. In step B, the purified titanium solution contains V ≤ 10 mg / L, Cr ≤ 10 mg / L, and Mn ≤ 20 mg / L; preferably V ≤ 5 mg / L, Cr ≤ 8 mg / L, and Mn ≤ 15 mg / L.

4. The method for deep purification of vanadium, chromium, and manganese in titanium dioxide solution using the sulfuric acid process according to claim 1, characterized in that: It also includes step C, where the bifunctional mesoporous silica adsorbent is regenerated by reverse desorption with an acidic reducing aqueous solution after adsorption saturation and then reused.

5. The method for deep purification of vanadium, chromium, and manganese in titanium dioxide solution using the sulfuric acid process according to claim 1, characterized in that: At least one of the following must be met: In step C, the acidic reducing aqueous solution is a mixture of 3~8wt% H2SO4 + 0.5~2wt% ascorbic acid; In step C, the flow rate for reverse desorption is 0.5~2.0 BV / h, the time is 3~6h, and the desorption efficiency is ≥95%. In step C, after reverse desorption, the bifunctionalized mesoporous silica adsorbent is washed with water until the washing solution pH ≥ 4 and then dried by nitrogen purging.

6. The method for deep purification of vanadium, chromium, and manganese in titanium dioxide solution using the sulfuric acid process according to claim 1, characterized in that: At least one of the following must be met: In step a, the molar ratio of tetraethyl orthosilicate to hexadecyltrimethylammonium bromide is 1:4~4.5; In step a, the amount of water used is 3-4 L of water for every 1 mol of tetraethyl orthosilicate; In step a, the hydrolysis-condensation reaction takes 15-25 hours; In step a, the roasting temperature is 500~600℃ and the time is 4~8h; In step a, the BET specific surface area of ​​the mesoporous silica matrix is ​​≥850 m². 2 / g, pore size 3.0~4.0nm, pore volume ≥0.95cm³ 3 / g.

7. The method for deep purification of vanadium, chromium, and manganese in titanium dioxide solution using the sulfuric acid process according to claim 1, characterized in that: At least one of the following must be met: In step b, the amount of toluene used is 0.8~1.2L per 100g of mesoporous silica matrix; In step b, the reflux reaction time is 4~12 hours; In step b, the drying process involves vacuum drying at 100-120℃ for 2-6 hours. In step b, the amino grafting density of the aminated mesoporous silica is 2.0~2.8 mmol / g.

8. The method for deep purification of vanadium, chromium, and manganese in titanium dioxide solution using the sulfuric acid process according to claim 1, characterized in that: At least one of the following must be met: In step c, the acidic medium is a 0.05~0.2 mol / L hydrochloric acid aqueous solution; In step c, the amount of acidic medium used is 1.5~2.5L of acidic medium added per 100g of aminated mesoporous silica; In step c, the reaction time is 8~16 hours; In step c, the drying process involves vacuum drying at 100~120℃ for 4~8 hours; In step c, the reaction conversion rate is controlled at 60-70%, so that 30-40% of unreacted amine groups are retained on the aminated mesoporous silica.

9. The method for deep purification of vanadium, chromium, and manganese in titanium dioxide solution using the sulfuric acid process according to claim 1, characterized in that: At least one of the following must be met: In step d, the volume ratio of ethanol to water in the ethanol / water mixed solvent is 3~5:1; In step d, the amount of ethanol / water mixed solvent used is 0.8~1.2L of ethanol / water mixed solvent added per 100g of aminophosphonic acid functionalized mesoporous silica; In step d, the condensation reaction takes 16-24 hours. In step d, the reduction reaction takes 10-16 hours. In step d, the drying process involves vacuum drying at 100~120℃ for 4~8 hours; In step d, the BET specific surface area of ​​the bifunctionalized mesoporous silica adsorbent is ≥620 m². 2 / g, pore volume ≥0.65cm 3 / g, the density of aminomethylenephosphonic acid groups is 1.6~1.7mmol / g, and the loading of 8-hydroxyquinoline groups is 0.45~0.60mmol / g.

10. The bifunctionalized mesoporous silica adsorbent as described in any one of claims 1 or 6 to 9 and its application in the purification of titanium liquid.

Citation Information

Patent Citations

  • Method for preparing titanium pigment by using titanium residues obtained by directly reducing titanium-iron oxide

    CN102627321A

  • Surface treatment enveloping process of rutile titanium dioxide

    CN103305033B

  • Method for acidolysis and reduction of ferric iron by titanium dioxide to improve quality of titaniferous solution through sulfuric acid method

    CN105271399A

  • Method for titaniferous solution reduction in sulfuric acid method based titanium dioxide production

    CN107954471A

  • Method for removing impurities from industrial metatitanic acid in the short-process process of sulfuric acid-based titanium dioxide

    CN114671460B